Determination of the impact of traffic delays at signalized intersections on the travel time of a fire engine to the place of a call - Pasnak, Ivan (Technology audit and production reserves, 2026)
The paper outlines the problem of the influence of various factors, in particular traffic delays at signalized intersections, on the movement of a fire engine to the place of a call. The object of research is the process of queue formation of vehicles at a signalized intersection, which leads to delays of a fire engine during its response. The conditions for queue formation at signalized intersections were identified, under which the queue may reach its maximum value or remain in a continuous growth mode. Thus, prerequisites for further research were established, and the maximum traffic flow intensity of 1000 passenger car units was selected. Using simulation modeling in the PTV Vissim environment, a model of a signalized intersection with a two-lane approach was developed. This model enables simulation of intersection crossing by varying traffic flow intensity, signal cycle length, and the proportion of green time within each cycle. Experimental studies of the maximum queue length were conducted using the full factorial experiment method. A relationship was obtained to determine the maximum queue length at a signalized intersection as a function of traffic flow intensity, signal cycle length, and the proportion of green time in each cycle. The magnitude of the influence of each identified parameter on queue formation at the intersection was analyzed separately. It was established that increasing the proportion of the green signal from 0.20 to 0.50 reduces the queue length by approximately 35–40%. An increase in traffic intensity from 200 to 1000 passenger car units per hour leads to an approximately fourfold increase in queue length. The obtained relationships can be further used in the development of new or the improvement of existing models for determining optimal response routes of emergency vehicles to the place of a call, taking into account possible delays at signalized intersections.